Pengembangan E-Modul Asam Basa Berbasis Inkuiri Terbimbing Berbantuan Flip PDF Professional untuk Meningkatkan Hasil Belajar Peserta Didik Kelas XI MIPA SMAN 3 Polewali - Indayani, Feby; Danial, Muhammad (Chemistry Education Review (CER), 2022)
This study is a development research, which aims at producing Acid-Based e-module based on guided inquiry assisted by Flip PDF Professional which is valid, practical, and effective. The development model used in this study was ADDIE development model, which consisted of analysis stage, design stage, development stage, implementation stage, and evaluation stage. The Acid-Base e-module based on guided inquiry developed was validated by two experts. After the validation, the Acid-Base e-module based on guided inquiry was tested to 37 students of grade XI MIPA at SMAN 3 Polewali. The e-module is stated as valid based on the validation result of e-module with the average 3.50 (very valid). The e-module has met the practical criteria based on the results: (1) the implementation of Acid-Base e-module based on guided inquiry with M = 1.79, which is in fully implemented category, (2) the teacher’s response is positive with 91.00%, which is in very practical category, and (3) the students’ responses are very positive with 84.24%, which is in practical category. The e-module is stated as effective based on the class completeness percentage which is shown in learning outcomes, 86.50%. Therefore, the result of the study indicates that the Acid-Base e-module based on guided inquiry assisted by Flip PDF Professional has valid, practical, and effective qualities.